(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article discusses the role of computer technology in learning foreign languages. It provides information based on examples about the communicative importance, efficiency, didactic role of using computer technologies in language education, and the possibilities of foreign language acquisition in this context.